Abnormally Expressed Ferroptosis-Associated FANCD2 in Mediating the Temozolomide Resistance and Immune Response in Glioblastoma - Song, Liying; Wu, Jiali; Fu, Hua; Wu, Cuifang; Tong, Xiaopei; Zhang, Mingyu (Frontiers in Pharmacology, 2022)
Ferroptosis related genes (FRGs) have been identified as potential targets involved in oncogenesis and cancer therapeutic response. Nevertheless, the specific roles and underlying mechanisms of FRGs in GBM and temozolomide (TMZ) resistance are largely unclear. Here, by using comprehensive bioinformatics, we verified that ferroptosis-related fanconi anemia complementation group D2 (FANCD2) was significantly upregulated in GBM tissues, and high level of FANCD2 was linked with the poor prognosis in primary and recurrent GBM patients. Moreover, FANCD2 was identified to promote TMZ resistance by attenuating ferroptosis in GBM cells. Knockdown of FANCD2 inhibited cell survival and increased reactive oxygen species (ROS) levels, two characteristics associated with ferroptosis, in TMZ-resistant GBM cells T98G-R and U118-R. KEGG pathway analysis indicated that aberrantly expressed FANCD2 was potentially linked with several cancer-associated signaling pathways, including chromosome segregation, DNA replication and cell cycle transition. In addition, we demonstrated that FANCD2 expression was positively linked with several tumor-infiltrating lymphocytes (TILs), such as Th2 cells, T helper cells and follicular helper T cells (TFH). Aberrant FANCD2 might also regulate multiple immune-associated signatures in GBM pathogenesis, such as immune-stimulators, immune-inhibitors, chemokines and their receptors. Therefore, upregulated FANCD2 could protect GBM cells from ferroptosis and promote TMZ resistance. Aberrantly expression of FANCD2 displayed a potential role in participating in immune microenvironment and ferroptosis. FANCD2 may be a novel therapeutic target in GBM.